Pengenalan dan Pembinaan Bahasa Arab melalui Game Edukatif di TKA/TPA - Nurul Fawzani; Nurjannah Nurjannah (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Arabic is a language that is contained in the Quran and is echoed until now. Apart from being the language of the scriptures, Arabic is a rich language and has its own uniqueness from a linguistic point of view. However, many still consider it a scourge because it is difficult to understand and so on. Through Arabic language development which is packaged in the form of creative and innovative learning such as educational games, it is hoped that it will be able to reduce and even erase negative opinions in the community about Arabic itself. TKA/TPA Al-Ikhtiar in Cinranae Hamlet, Lamatti Riaja Village, Bulupoddo District, as an Islamic religious education institution is one of the objects for conducting Arabic language development from an early age. This is done so that children can recognize and know that Arabic is not as difficult as most people think. The results show that learning Arabic through educational games increases students' interest in learning Arabic.Keywords: Coaching, Arabic, Educational Games.